Septic arthritis in Western and sub-Saharan African children - a review. - Lavy, C (2007)
This article reviews what is known about the incidence, aetiology, presentation, bacteriology and management of septic arthritis in children. It compares where possible the different presentations and characteristics of this condition in the Western and sub-Saharan African regions.